A precursor of a gel-like curable strong adhesion tissue adhesive and its preparation method and use method

By introducing materials such as sodium hyaluronate into bioadhesives to form a crosslinking network, the shortcomings of existing bioadhesives in adhesion strength and biocompatibility are solved, and efficient and stable in complex surgery are achieved Wound sealing effect.

CN116059436BActive Publication Date: 2024-12-24BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310038999.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2024-12-24
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

Existing bioadhesives have shortcomings in adhesion strength and biocompatibility, especially in the presence of blood and tissue exudate, and are difficult to meet the wound sealing needs in complex surgeries.

Method used

Using a precursor of a gel-like curable strong adhesion tissue adhesive, sodium hyaluronate, N-(2-amino-2-oxyethyl)acrylamide, and N-succinimide acrylic acid Compositional materials such as esters, sodium alginate and inorganic salts are mixed, and polymerized by ultraviolet light to form a chemical and physical crosslinking network to improve the cohesion and surface adhesion of the adhesive.

Benefits of technology

It achieves high adhesion strength and low swelling rate in a humid environment, can effectively adhere and fix soft and hard tissues, has good anti-fatigue and anti-destructive properties, and is suitable for wound sealing in complex surgeries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116059436B_ABST
    Figure CN116059436B_ABST
Patent Text Reader

Abstract

The invention discloses a precursor of a gel-like curable strong adhesion tissue adhesive, which comprises, by mass, 10 parts of sodium hyaluronate with a double bond grafting rate of 10 to 100%, 1000 to 3000 parts of N-(2-amino-2-oxyethyl) acrylamide, 100 to 500 parts of acrylic acid-N-succinimide ester, 100 to 400 parts of sodium alginate, 5 to 20 parts of inorganic salt, 1 to 50 parts of initiator, and 10,000 parts of solvent. The gel-like adhesive precursor is applied to biological tissue to absorb tissue surface water. Under ultraviolet light, the gel-like adhesive precursor can be quickly cured and achieve in-situ rapid strong adhesion with biological tissue. The adhesive has good strength, toughness and low swelling at the same time, and can be widely used in dry and wet tissue sealing and repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials and relates to a precursor of a gel-like curable strong-adhesion tissue adhesive and a preparation method and an application method thereof. Background Art

[0002] In clinical practice, suturing is the main method used to heal surgical wounds. Although this method is widely applicable and has good therapeutic effects, it is complex to operate and has high requirements for suturing strength and position. Scars may be left on the wound after surgery. In addition, it is difficult to close wounds with sutures in many scenarios, such as some soft tissue organs, such as eyes, liver, small intestine, and blood vessels. Therefore, it is necessary to develop a biomaterial that is easy to operate and can seal wounds to cope with some complex surgeries that are difficult to suture clinically, and to promote medical progress through material innovation and development.

[0003] Bioadhesive is a polymer material that can form strong adhesion with biological tissue and seal wounds. It is easy to use, has good adhesion effect, and good biocompatibility. It has developed rapidly in recent years. At present, commercial bioadhesives include fibrin glue, cyanoacrylate glue, etc. Fibrin glue is an adhesive with good biocompatibility, but its adhesion strength is low. Although cyanoacrylate glue has good adhesion to dry tissue, it has very low adhesion when there is blood and tissue exudate, and it is highly toxic. Ideal bioadhesives include the following aspects: 1) biocompatibility, no cytotoxicity; 2) chemical stability to ensure strong adhesion; 3) mechanical matching with the adhered tissue; 4) resistance to fatigue and damage imposed by tissue; 5) appropriate swelling to prevent squeezing of tissue; 6) biodegradation. Of course, the design of bioadhesives also needs to be combined with application scenarios.

[0004] The bonding effect of adhesives depends mainly on two factors: the cohesion of the adhesive and the surface adhesion. Cohesion refers to the intermolecular attraction between molecules of the same substance, and is also the force between the molecules of the adhesive itself, that is, the strength of the adhesive. These forces include: 1) chemical bonds within the adhesive polymer; 2) chemical bonds generated by polymer crosslinking; 3) intermolecular interactions in the adhesive; 4) mechanical adhesion between various molecules in the adhesive. Adhesion (also known as adhesion) refers to the attraction between molecules of different substances, which is the tendency of different molecules to attract each other. It mainly refers to the force between the adhesive and the adherend, that is, the force of the adhesive adhering to the surface of the object. The adhesion phenomenon is caused by the molecular interaction between the substrate surface and the adhesive, so these effects include weak intermolecular interactions as well as strong chemical bonds. In addition to intermolecular and chemical adhesion, depending on the morphology of the substrate surface, the adhesive can effectively "mechanically adhere" to the rough substrate surface by filling the gaps in the rough surface.

[0005] As a biological adhesive, when the adhesive is applied to damaged biological tissue, in addition to considering the cohesion and surface adhesion of the adhesive, it also needs to face the following challenges: 1) When the adhesive is a living organism, its activity characteristics need to be considered. When a living organism is applied, if the surface is irregular, especially if the body surface is smooth and often curved, the liquid is easy to slide off, and it is difficult to maintain a fixed posture for a long time, and it is easy to shake slightly. Therefore, when the adhesive is applied, it needs to achieve ease of use, and it can have good stagnation on the curved surface without flowing away; at the same time, it can still maintain good adhesion under slight activities. 2) Biological tissue contains a lot of water, and when the tissue is traumatized, there will be varying degrees of bleeding and exudation. These liquids may become a medium that hinders the contact between the adhesive and the tissue surface, affecting the surface adhesion of the adhesive. Therefore, biological adhesives suitable for living tissues should have the characteristics of water absorption. After absorbing interfacial water, the adhesive can fully contact the surface to be adhered, thereby providing good surface adhesion.

[0006] Hydrogel is a type of extremely hydrophilic three-dimensional network structure gel that can swell rapidly in water and can hold a large volume of water in this swollen state without dissolving. The unique water absorption and swelling properties of hydrogel can effectively and quickly remove interfacial water from wet surfaces, allowing its three-dimensional network structure to effectively contact the surface. Therefore, it is expected to become a solution strategy for the effect of exudate on surface adhesion when bioadhesives are applied to tissue surfaces. In addition, hydrogels can be divided into chemically cross-linked and physically cross-linked hydrogels. Chemical cross-linking consists of covalent bonds between polymer chains. Due to the high bond energy of covalent bonds, chemically cross-linked hydrogels have high cross-linking strength, good mechanical properties, and high cohesive energy. However, due to the irreversibility of chemical cross-linking, chemically cross-linked hydrogels have poor deformation ability and are fragile. Physically cross-linked hydrogels are cross-linked by hydrogel skeletons through physical effects such as hydrogen bonds, hydrophobic interactions, and chain entanglements. Most of these physical effects are reversible and can be cross-linked again after breaking, thereby providing good energy dissipation for hydrogels and giving hydrogels good deformation ability. These two cross-linking properties of hydrogels are also expected to become a solution to meet the bonding needs of bioadhesives. Specifically: 1) Chemical cross-linking can effectively improve the cross-linking strength inside the hydrogel, thereby significantly improving the cohesion of the body and achieving adhesion. 2) Physical cross-linking can provide hydrogels with good plasticity, so that they can be applied to the tissue that needs to be adhered to, and achieve conformal filling of uneven surfaces and surfaces with gaps. However, due to the special application method of bioadhesives, the adhesive needs to be evenly applied to the gaps of the wound before achieving good adhesion. The existing hydrogel chemical, physical or mixed cross-linking methods cannot meet the use conditions of medical adhesives.

[0007] Photocurable hydrogel refers to a hydrogel that forms a three-dimensional network structure by polymerization initiated by visible light or ultraviolet light. This type of hydrogel is generally obtained by initiating polymerization of a precursor composed of a prepolymer (also known as an oligomer), an active monomer and a photoinitiator under light source irradiation. Under the irradiation of the light source, the photoinitiator in the precursor absorbs energy of a certain wavelength to produce free radicals, cations, etc., thereby initiating monomer polymerization and cross-linking to form a polymer network. As the network cross-linking density increases, a cured hydrogel is formed. Although this photocuring gelling method provides a technical solution for constructing chemically bonded hydrogels, since the precursor is a flowing liquid, it is easy to flow and cannot be fixed, and it still cannot fully meet the needs of bioadhesives to be applied and stay on the wound. In order to further optimize the photocurable hydrogel to meet the technical requirements of bioadhesives, the pre-introduction of the first physical cross-linking network in the prepolymer of the photocurable hydrogel can give the prepolymer a gel-like property, so that it can be evenly applied and stay in the gap of the damaged tissue, and then through the photocuring method, the cross-linking of the prepolymer and the monomer is initiated to form a second network chemical cross-linking, thereby strengthening the cohesive force of the adhesive. Summary of the invention

[0008] In view of this, the present invention provides a precursor of a gel-like curable strong adhesion tissue adhesive and a preparation method and application method thereof. The present invention specifically provides the following technical solutions:

[0009] 1. A precursor of a gel-like curable strong adhesion tissue adhesive, which comprises, by weight, 10 parts of sodium hyaluronate with a double bond grafting rate of 10 to 100%, 1000 to 3000 parts of N-(2-amino-2-oxyethyl) acrylamide, 100 to 500 parts of acrylic acid-N-succinimide ester, 100 to 400 parts of sodium alginate, 5 to 20 parts of inorganic salt, 1 to 50 parts of initiator, and 10,000 parts of solvent.

[0010] Furthermore, in terms of mass fractions, the double bond grafting rate is 50%, including 10 parts of sodium hyaluronate, 2000-3000 parts of N-(2-amino-2-oxyethyl) acrylamide, 200-500 parts of acrylic acid-N-succinimide ester, 200 parts of sodium alginate, 5-20 parts of inorganic salt, 1-50 parts of initiator, and 10,000 parts of solvent.

[0011] Furthermore, the inorganic salt includes calcium sulfate, calcium chloride, and calcium carbonate.

[0012] Furthermore, the initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt or α-ketoglutaric acid.

[0013] Furthermore, the solvent includes deionized water, phosphate buffer or Tris buffer.

[0014] 2. The preparation method of the above-mentioned precursor of a gel-like curable strong adhesion tissue adhesive is prepared according to the following steps:

[0015] 1) preparing sodium hyaluronate containing double bonds;

[0016] 2) mixing the double-bond-containing sodium hyaluronate obtained in step 1), N-(2-amino-2-oxyethyl)acrylamide, acrylic acid-N-succinimidyl ester, an initiator and a solvent to obtain a mixed solution 1;

[0017] 3) The mixed solution 1 obtained in step 2) is evenly mixed with sodium alginate and an inorganic salt to obtain a gel-like adhesive precursor.

[0018] Furthermore, the mixed solution 1 obtained in step 2) is a liquid and is not easy to stay on a smooth surface. The adhesive precursor obtained in step 3) is a gel, has good spreadability and conformal filling properties, can be applied to the gaps on the surface, has a liquid absorption rate of 230% to 300%, and can absorb the interfacial water on the surface of wet tissues so that the wet tissues can adhere in situ.

[0019] 3. A method for using the above-mentioned precursor of a gel-like curable strong adhesion tissue adhesive is to apply the gel-like adhesive precursor to biological tissue, and irradiate it with an ultraviolet light source with a wavelength of 250 to 400 nm for less than 1 minute. The precursor of the gel-like adhesive is quickly cured and strongly adheres to the biological tissue.

[0020] Furthermore, after being cured by light, the gel-like adhesive precursor has a maximum swelling rate of 22% to 80% in a wet environment.

[0021] Furthermore, the gel adhesive precursor can produce an adhesive effect on skin, soft tissue organs, and hard tissue after light curing, with a shear tensile bearing strength of 90 to 300 kPa and a T-peel tensile bearing strength of 350 to 1000 J·m -2 , tensile strength of 200-500 kPa and wound closure strength of 50-200 kPa.

[0022] The beneficial effects of the present invention are:

[0023] 1. The adhesive precursor of the present invention is a gel precursor that can be applied or injected on the surface of tissues, fill the surface and gaps of tissues in a conforming manner, and stay on the surface of tissues. It can ensure that it fills and stays in any tissue, such as soft tissues (eyes, mucous membranes, etc.) and hard tissues (bone, tendon), etc.

[0024] 2. The adhesive precursor of the present invention can absorb water at the tissue interface, thereby achieving wet tissue adhesion.

[0025] 3. The adhesive precursor of the present invention can quickly gel within a few seconds to tens of seconds under ultraviolet light, which can achieve rapid adhesion while ensuring that the adhesive has high strength and is not easily damaged.

[0026] 4. After the adhesive precursor of the present invention is gelled in a very short time, the adhesive body strength is relatively high. This is because under the irradiation of ultraviolet light, the initiator decomposes to produce free radicals, which then triggers the polymerization of N-(2-amino-2-oxyethyl) acrylamide to obtain poly(N-(2-amino-2-oxyethyl) acrylamide), which itself forms a strong double hydrogen bond to ensure a certain body strength. In addition, sodium hyaluronate and N-(2-amino-2-oxyethyl) acrylamide with a certain double bond grafting rate are polymerized to provide stable chemical cross-linking sites and constitute the first cross-linking network. Moreover, sodium alginate and calcium ions form ionic bonds, serving as the second physical cross-linking network. When the double-network hydrogel structure is subjected to mechanical damage, the hydrogen bonds between poly(N-(2-amino-2-oxyethyl)acrylamide) and the ionic bonds between sodium alginate and calcium ions act as mechanical dissipation mechanisms, and the chemical cross-linking provided by the double-bond grafted sodium hyaluronate after polymerization ensures the stability of the hydrogel. The synergistic effect of the two gives the hydrogel higher mechanical strength and toughness, thereby resisting the extrusion, impact, and tearing of the adhesive by tissues and organs.

[0027] 5. The adhesive precursor of the present invention can produce strong adhesion to the tissue during the gelation process. The mechanism of strong adhesion to the tissue is, on the one hand, that N-(2-amino-2-oxyethyl) acrylamide quickly polymerizes into gel, forming hydrogen bonds and mechanical interlocking with the tissue. On the other hand, acrylic acid-N-succinimidyl ester can quickly form amide bonds with the amino groups on the tissue, so that the adhesive and the tissue form a stable chemical adhesion, which can increase the adhesion strength by several times or even an order of magnitude. This is because when testing the adhesion strength between the adhesive and the tissue, on the one hand, the toughness of the adhesive itself dissipates part of the energy; on the other hand, the interaction between the adhesive and the tissue also dissipates part of the energy. First, the weak physical adhesion effect debonds first, and finally the strong chemical adhesion debonds. Combining the above two factors, the overall adhesion strength of the adhesive is much higher than that of other adhesives.

[0028] 6. The adhesive disclosed in the present invention also has anti-swelling properties. In this way, after the adhesive adheres to the tissue, although it is in a humid environment, the adhesive will not be destroyed due to body swelling. This is because the first cross-linked network composed of sodium alginate and inorganic salts in the adhesive precursor has a second cross-linked network formed by sodium hyaluronate and N-(2-amino-2-oxyethyl) acrylamide after curing, and the strong hydrogen bonding effect formed between the cured poly(N-(2-amino-2-oxyethyl) acrylamide). These synergistic effects can effectively prevent water molecules from destroying the gel network and keep the adhesive with a low swelling rate.

[0029] 7. The adhesive disclosed in the present invention also has the property of long-term adhesion to moist tissues. This is due to the synergistic effect of the adhesive's physical and chemical adhesion to tissues and its own low swelling rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings:

[0031] Figure 1 The flow photographs of the adhesive precursors of Examples 1-4 and Comparative Examples 1-3 on the back of the hand are shown.

[0032] Figure 2 The viscosity and shear rate curves of the adhesive precursors of Examples 1-4 and Comparative Examples 2 and 3 are shown.

[0033] Figure 3 This is the frequency sweep result of the rheometer test after the adhesive precursor of Example 5 is gelled.

[0034] Figure 4 This is the shear tensile strength curve of the adhesive precursor of Example 10 after in-situ gelation on pig skin and tested in a universal mechanical testing machine.

[0035] Figure 5 This is the tensile strength curve of the adhesive precursor of Example 10 after in-situ gelation on pig skin and tested in a universal mechanical testing machine.

[0036] Figure 6 is the swelling curve of the adhesive of Example 11 in deionized water. DETAILED DESCRIPTION

[0037] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.

[0038] Example 1

[0039] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0040] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0041] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1), 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 100 mg of sodium alginate, 10 mg of calcium sulfate, and 15 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0042] 2. Test the fluidity and viscosity of the above adhesive precursor. The specific test method is as follows:

[0043] 1) Inject the adhesive precursor into the back of the hand, then tilt it and take a photo to record the flow of the precursor.

[0044] 2) Inject the adhesive precursor into the rheometer platform, set relevant parameters, and obtain the viscosity and shear rate curve.

[0045] The flow photograph of the adhesive precursor prepared in Example 1 on the back of the hand is shown in Figure 1 ,from Figure 1 It can be seen that the precursor is in a gel-like state and stays steadily on the back of the hand, and is not easy to flow away even when tilted.

[0046] The viscosity and shear rate curve of the adhesive precursor prepared in Example 1 is shown in Figure 2 The viscosity of the precursor was measured to be approximately 15.45 Pa·s and the shear stress was 1.55 Pa.

[0047] Example 2

[0048] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0049] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0050] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 15 mg of calcium sulfate, and 15 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0051] 2. Test the fluidity and viscosity of the above adhesive precursor. The specific test method is as follows:

[0052] 1) Inject the adhesive precursor into the back of the hand, then tilt it and take a photo to record the flow of the precursor.

[0053] 2) Inject the adhesive precursor into the rheometer platform, set relevant parameters, and obtain the viscosity and shear rate curve.

[0054] The photo of the flow of the adhesive precursor of Example 2 on the back of the hand is shown in Figure 1 .from Figure 1 It can be seen that the precursor is in a gel-like state and stays steadily on the back of the hand, and is not easy to flow away even when tilted.

[0055] The viscosity and shear rate curve of the adhesive precursor of Example 2 is shown in Figure 2 The viscosity of the precursor was measured to be 58.65 Pa·s and the shear stress was 5.87 Pa.

[0056] Example 3

[0057] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0058] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0059] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 300 mg of sodium alginate, 5 mg of calcium sulfate, and 15 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0060] 2. Test the fluidity and viscosity of the above adhesive precursor. The specific test method is as follows:

[0061] 1) Inject the adhesive precursor into the back of the hand, then tilt it and take a photo to record the flow of the precursor.

[0062] 2) Inject the adhesive precursor into the rheometer platform, set relevant parameters, and obtain the viscosity and shear rate curve.

[0063] The photo of the flow of the adhesive precursor of Example 3 on the back of the hand is shown in Figure 1 .from Figure 1 It can be seen that the precursor is in a gel-like state and stays steadily on the back of the hand, and is not easy to flow away even when tilted.

[0064] The viscosity and shear rate curve of the adhesive precursor of Example 3 is shown in Figure 2 The viscosity of the precursor was measured to be 15.22 Pa·s and the shear stress was 1.22 Pa.

[0065] Example 4

[0066] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0067] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0068] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 400 mg of sodium alginate, 20 mg of calcium sulfate, and 15 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0069] 2. Test the fluidity and viscosity of the above adhesive precursor. The specific test method is as follows:

[0070] 1) Inject the adhesive precursor into the back of the hand, then tilt it and take a photo to record the flow of the precursor.

[0071] 2) Inject the adhesive precursor into the rheometer platform, set relevant parameters, and obtain the viscosity and shear rate curve.

[0072] The photo of the flow of the adhesive precursor of Example 4 on the back of the hand is shown in Figure 1 .from Figure 1It can be seen that the precursor is in a gel-like state and stays steadily on the back of the hand, and is not easy to flow away even when tilted.

[0073] The viscosity and shear rate curve of the adhesive precursor of Example 4 is shown in Figure 2 The viscosity of the precursor was measured to be 523.92 Pa·s and the shear stress was 52.41 Pa.

[0074] Example 5

[0075] 1. The preparation steps of a gel-like curable strong adhesion tissue adhesive precursor are as follows:

[0076] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 2 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 10%.

[0077] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 10%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 5 mg of calcium sulfate, and 5 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0078] 2. The method of using the above adhesive precursor is as follows:

[0079] The adhesive precursor is applied to the biological tissue and irradiated with 365 nm ultraviolet light for 20 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0080] Figure 3 The frequency sweep result of the rheometer test after the adhesive precursor of Example 5 was gelled. Figure 3 It can be seen that the storage modulus G' is greater than the loss modulus G" in the range of 1-100 rad / s, indicating that it is in a gel state. Moreover, as the frequency increases, G' remains basically stable, indicating that the hydrogel has good stability.

[0081] Example 6

[0082] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0083] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0084] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 15 mg of calcium sulfate, and 4 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed uniformly in 10 mL of phosphate buffer to obtain an adhesive precursor.

[0085] 2. The method of using the above adhesive precursor is as follows:

[0086] The adhesive precursor is applied to the biological tissue and irradiated with 365 nm ultraviolet light for 40 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0087] Example 7

[0088] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0089] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 25 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 100%.

[0090] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 100%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 10 mg of calcium chloride, and 1 mg of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate are mixed uniformly in 10 mL of tris(hydroxymethyl)aminomethane buffer to obtain an adhesive precursor.

[0091] 2. The method of using the above adhesive precursor is as follows:

[0092] The adhesive precursor is applied to the biological tissue and irradiated with 284 nm ultraviolet light for 5 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0093] Example 8

[0094] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0095] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0096] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 1000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 5 mg of calcium carbonate, and 5 mg of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate are mixed uniformly in 10 mL of phosphate buffer to obtain an adhesive precursor.

[0097] 2. The method of using the above adhesive precursor is as follows:

[0098] The adhesive precursor is applied to the biological tissue and irradiated with 365nm ultraviolet light for 45s to make the adhesive gel and adhere tightly to the biological tissue.

[0099] Example 9

[0100] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0101] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0102] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 2000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 5 mg of calcium chloride, and 6 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0103] 2. The method of using the above adhesive precursor is as follows:

[0104] The adhesive precursor is applied to the biological tissue and irradiated with 365nm ultraviolet light for 25s to make the adhesive gel and adhere tightly to the biological tissue.

[0105] Example 10

[0106] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0107] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0108] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 100 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 15 mg of calcium sulfate, and 12 mg of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were mixed uniformly in 10 mL of phosphate buffer to obtain an adhesive precursor.

[0109] 2. The method of using the above adhesive precursor is as follows:

[0110] The adhesive precursor is applied to the biological tissue and irradiated with 284 nm ultraviolet light for 10 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0111] Figure 4 This is the shear tensile strength curve of the adhesive precursor of Example 10 after in-situ gelation on pig skin, tested in a universal mechanical testing machine. Figure 4 It can be seen that the shear tensile bearing strength of Example 10 on pig skin is about 150 kPa, which is a high adhesion strength in the field of tissue adhesion.

[0112] Figure 5 This is the tensile strength curve of the adhesive precursor of Example 10 after in-situ gelation on pig skin and tested in a universal mechanical testing machine. Figure 5 It can be seen that the tensile strength of Example 10 on pig skin is about 280 kPa, which is a high adhesion strength in the field of tissue adhesion.

[0113] Embodiment 11

[0114] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the specific steps are as follows:

[0115] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0116] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 500 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 10 mg of calcium carbonate, and 5 mg of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate are mixed uniformly in 10 mL of tris(hydroxymethyl)aminomethane buffer to obtain an adhesive precursor.

[0117] 2. The method of using the above adhesive precursor is as follows:

[0118] The adhesive precursor is applied to the biological tissue and irradiated with 395 nm ultraviolet light for 10 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0119] Figure 6 is the swelling curve of the adhesive of Example 11 in deionized water. Figure 6 It can be seen that the equilibrium swelling ratio of the adhesive is about 60%, which belongs to the low swelling category in the swelling properties of hydrogels.

[0120] Comparative Example 1

[0121] In this example, sodium alginate and calcium sulfate were not added.

[0122] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0123] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0124] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, and 15 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed uniformly in 10 mL of deionized water to obtain an adhesive precursor.

[0125] 2. Test the fluidity and viscosity of the above adhesive precursor. The specific test method is as follows:

[0126] 1) Inject the adhesive precursor into the back of the hand, then tilt it and take a photo to record the flow of the precursor.

[0127] 2) Inject the adhesive precursor into the rheometer platform, set relevant parameters, and obtain the viscosity and shear rate curve.

[0128] The flow photo of the adhesive precursor of Comparative Example 1 on the back of the hand is shown in Figure 1 .from Figure 1 It can be seen that the precursor cannot stay on the back of the hand, similar to the state of a solution, and the viscosity and shear stress cannot be measured on the rotational rheometer. This is because the adhesive precursor lacks the cross-linking of sodium alginate and calcium ions, and other solutes are completely dissolved in the solution, without any viscosity.

[0129] Comparative Example 2

[0130] In this example, no sodium alginate was added.

[0131] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0132] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0133] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 20 mg of calcium sulfate, and 15 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0134] 2. Test the fluidity and viscosity of the above adhesive precursor. The specific test method is as follows:

[0135] 1) Inject the adhesive precursor into the back of the hand, then tilt it and take a photo to record the flow of the precursor.

[0136] 2) Inject the adhesive precursor into the rheometer platform, set relevant parameters, and obtain the viscosity and shear rate curve.

[0137] The flow photo of the adhesive precursor of Comparative Example 2 on the back of the hand is shown in Figure 1 .from Figure 1It can be seen that the precursor cannot stay when the back of the hand is tilted. This is because without sodium alginate, calcium sulfate alone cannot cross-link and the viscosity of the precursor is still very low.

[0138] The viscosity and shear rate curve of the adhesive precursor of Comparative Example 2 is shown in Figure 2 The viscosity of the precursor was measured to be 0.31 Pa·s and the shear stress was 0.03 Pa.

[0139] Comparative Example 3

[0140] In this example, no calcium sulfate was added.

[0141] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0142] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0143] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 400 mg of sodium alginate, and 15 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0144] 2. Test the fluidity and viscosity of the above adhesive precursor. The specific test method is as follows:

[0145] 1) Inject the adhesive precursor into the back of the hand, then tilt it and take a photo to record the flow of the precursor.

[0146] 2) Inject the adhesive precursor into the rheometer platform, set relevant parameters, and obtain the viscosity and shear rate curve.

[0147] The flow photograph of the adhesive precursor of Comparative Example 3 on the back of the hand is shown in Figure 1 .from Figure 1 It can be seen that the precursor can stay for a certain period of time when the back of the hand is tilted, but there will be obvious signs of flow. This is because when only sodium alginate (without calcium sulfate) exists, the physical entanglement of macromolecules shows an increase in viscosity, but the entanglement effect is relatively weak and cannot guarantee good stability.

[0148] The viscosity and shear rate curve of the adhesive precursor of Comparative Example 3 is shown in Figure 2The viscosity of the precursor was measured to be 3.42 Pa·s and the shear stress was 0.34 Pa.

[0149] Comparative Example 4

[0150] In this example, sodium hyaluronate is not double-bond modified with methacrylic anhydride.

[0151] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0152] 1) 10 mg of sodium hyaluronate without double bond modification (Mn=300 kDa), 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimidyl ester, 200 mg of sodium alginate, 15 mg of calcium sulfate, and 5 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed uniformly in 10 mL of deionized water to obtain an adhesive precursor.

[0153] 2. The method of using the above adhesive precursor is as follows:

[0154] The adhesive precursor is applied to the biological tissue and irradiated with 365 nm ultraviolet light for 30 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0155] Comparative Example 5

[0156] In this example, N-(2-amino-2-oxyethyl)acrylamide was not added.

[0157] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0158] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0159] 2) 100 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 5 mg of calcium chloride, and 25 mg of α-ketoglutaric acid were mixed evenly in 10 mL of deionized water to obtain an adhesive precursor.

[0160] 2. The method of using the above adhesive precursor is as follows:

[0161] The adhesive precursor is applied to the biological tissue and irradiated with 254 nm ultraviolet light for 60 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0162] Comparative Example 6

[0163] In this example, a small amount of N-(2-amino-2-oxyethyl)acrylamide was added.

[0164] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0165] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0166] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 500 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 5 mg of calcium chloride, and 15 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0167] 2. The method of using the above adhesive precursor is as follows:

[0168] The adhesive precursor is applied to the biological tissue and irradiated with 365 nm ultraviolet light for 30 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0169] Comparative Example 7

[0170] In this example, an excess of N-(2-amino-2-oxyethyl) acrylamide was added.

[0171] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0172] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0173] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 4000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 5 mg of calcium chloride, and 20 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0174] 2. The method of using the above adhesive precursor is as follows:

[0175] The adhesive precursor is applied to the biological tissue and irradiated with 394 nm ultraviolet light for 55 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0176] Comparative Example 8

[0177] In this example, no N-succinimidyl acrylate was added.

[0178] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0179] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0180] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 200 mg of sodium alginate, 5 mg of calcium chloride, and 6 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone were mixed in 10 mL of deionized water to obtain an adhesive precursor.

[0181] 2. The method of using the above adhesive precursor is as follows:

[0182] The adhesive precursor is applied to the biological tissue and irradiated with 365nm ultraviolet light for 25s to make the adhesive gel and adhere tightly to the biological tissue.

[0183] Comparative Example 9

[0184] In this example, a small amount of N-succinimidyl acrylate was added.

[0185] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0186] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0187] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 50 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 5 mg of calcium chloride, and 10 mg of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate are mixed uniformly in 10 mL of deionized water to obtain an adhesive precursor.

[0188] 2. The method of using the above adhesive precursor is as follows:

[0189] The adhesive precursor is applied to the biological tissue and irradiated with 254 nm ultraviolet light for 10 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0190] Comparative Example 10

[0191] In this example, an excess of N-succinimidyl acrylate was added.

[0192] 1. Prepare a gel-like curable strong adhesion tissue adhesive precursor, the steps are as follows:

[0193] 1) Weigh 1 g of sodium hyaluronate (Mn=300 kDa), dissolve it in 100 mL of deionized water, add 10 mL of methacrylic anhydride, stir evenly, adjust the pH to 8-9 with 5 mol / L sodium hydroxide solution, react at 4°C for 24 h, dialyze for 3 days, filter, and freeze-dry to obtain methacrylic anhydride-modified sodium hyaluronate with a double bond grafting rate of 50%.

[0194] 2) 10 mg of methacrylic anhydride-modified sodium hyaluronate (double bond grafting rate of 50%) obtained in step 1, 3000 mg of N-(2-amino-2-oxyethyl) acrylamide, 800 mg of acrylic acid-N-succinimide ester, 200 mg of sodium alginate, 5 mg of calcium sulfate, and 40 mg of α-ketoglutaric acid were mixed uniformly in 10 mL of deionized water to obtain an adhesive precursor.

[0195] 2. The method of using the above adhesive precursor is as follows:

[0196] The adhesive precursor is applied to the biological tissue and irradiated with 365 nm ultraviolet light for 40 seconds to make the adhesive gel and adhere tightly to the biological tissue.

[0197] Test Example 1

[0198] Comparative Examples 1-3 and Examples 1-4 were placed on a smooth glove at an angle to simulate a real tilting condition, and their morphologies were observed and recorded. The viscosity-shear rate curves of these adhesive precursors were measured using a rotational rheometer, and the corresponding viscosities and shear stresses were measured, as shown in Table 1.

[0199] Table 1 Adhesive precursor viscosity and state

[0200]

[0201]

[0202] As can be seen from Table 1, according to the technical solution of the present invention, without adding sodium alginate and calcium sulfate components (Comparative Example 1) or adding only one of the components (Comparative Examples 2 and 3), the prepared adhesive precursors are all liquid, have strong fluidity, cannot adhere to the surface, and will slide down with gravity when tilted ( Figure 1 ).

[0203] According to the present invention, Examples 1-4 all present a gel state, and the viscosity thereof is also increased from 0.31 to 3.42 Pa·s of the comparative example to 15.22 to 523.92 Pa·s, and the shear stress is increased from 0.03 to 0.34 Pa of the comparative example to 1.22 to 52.41 Pa. This shows that the sodium alginate and calcium-containing inorganic salt (such as calcium sulfate) components disclosed in the formula are indispensable, and the physical cross-linked network constructed by these two components can give the adhesive precursor a gel-like property, which can meet the requirements of spreadability and conformable filling during application. In addition, the improved viscosity can enable the adhesive precursor to effectively adhere without falling off, and the improved shear stress enables the adhesive precursor to maintain good elasticity under the action of external force and gravity, and can maintain its original shape.

[0204] According to YY / T 0729 “Test Method for Adhesive Properties of Tissue Adhesives”, the shear tensile bearing strength, T-peel tensile bearing strength, tensile strength and wound closure strength of the hydrogels of Comparative Examples 4-10 and Examples 5-11 were tested, and Table 2 was obtained.

[0205] Table 2 Adhesive adhesion performance test

[0206]

[0207]

[0208] It can be seen from Table 2 that by testing the mechanical properties of the embodiments, the shear tensile bearing strength of the embodiments 5-11 of the present invention is 90-300 kPa, and the T-peel tensile bearing strength is 350-1000 J·m -2 , the tensile strength is 200-500 kPa and the wound closure strength is 50-200 kPa. The shear tensile bearing strength, T-peeling tensile bearing strength, tensile strength and wound closure strength of the embodiment are all higher than those of the comparative example, and the shear tensile bearing strength, T-peeling tensile bearing strength, tensile strength and wound closure strength are related to the double bond grafting rate of sodium hyaluronate, the mass fractions of N-(2-amino-2-oxyethyl) acrylamide and acrylic acid-N-succinimidyl ester.

[0209] In the adhesive precursor formula claimed for protection in the present invention, the double bond grafting rate of sodium hyaluronate, the mass fractions of N-(2-amino-2-oxyethyl) acrylamide and acrylic acid-N-succinimide ester are defined at the same time. The sodium hyaluronate grafted with double bonds in the adhesive provides rigidity and mechanical support, sodium alginate and calcium ions provide energy dissipation, and at the same time, the hydrogen bonding effect of N-(2-amino-2-oxyethyl) acrylamide itself can not only provide the toughness of the hydrogel, but also form a strong hydrogen bonding effect with the tissue. Moreover, acrylic acid-N-succinimide ester can chemically adhere to the amino groups on the tissue, and the hydrogen bonding adhesion with N-(2-amino-2-oxyethyl) acrylamide synergistically enhances the adhesion strength of the adhesive. Specifically:

[0210] (1) The double bond grafting rate of sodium hyaluronate has a significant effect on the final adhesion performance.

[0211] When the double bond grafting rate of hyaluronic acid is 0 (Comparative Example 4), the adhesive strength of the constructed adhesive is extremely low (the shear tensile bearing strength is only 20 kPa, and the T-peel tensile bearing strength is only 100 J·m -2 , tensile strength is only 33 kPa, and wound closure strength is only 12 kPa), which cannot meet the needs of adhesion. As the double bond grafting rate of sodium hyaluronate increases, the adhesion performance shows a trend of first increasing and then decreasing (the grafting rates of Examples 5, 6 and 7 are 10%, 50% and 100%, respectively). When the grafting rate of sodium hyaluronate is low (10% in Example 5), there are fewer double bonds involved in the polymerization, the chemical cross-linking density is low, the hydrogen bonding effect of N-(2-amino-2-oxyethyl) acrylamide itself is strong, and the hydrogen bonding effect with the tissue is also more, but the adhesive itself has a low body strength (low chemical cross-linking density), resulting in shear tensile bearing strength (189 kPa), T-peel tensile bearing strength (633 J·m -2), tensile strength (356 kPa) and wound closure strength (120 kPa) are low. When the grafting rate of sodium hyaluronate is high (100% in Example 7), there are more double bonds involved in the polymerization, the chemical crosslinking density is high, the hydrogen bonding effect of N-(2-amino-2-oxyethyl) acrylamide itself is weak, the hydrogen bonding effect with the tissue is also less, and the adhesive body strength is also low (the chemical crosslinking density is high), resulting in the shear tensile bearing strength (136 kPa), T-peel tensile bearing strength (413 J·m -2 ), tensile strength (248 kPa) and wound closure strength (88 kPa) were lower. When sodium hyaluronate had an appropriate double bond grafting ratio (50% in Example 6), shear tensile bearing strength (232 kPa), T-peel tensile bearing strength (754 J·m -2 ), tensile strength (403 kPa) and wound closure strength (136 kPa) are relatively high. Therefore, a 50% sodium hyaluronate grafting rate is preferred to ensure that the hydrogel has good mechanical properties and tissue adhesion.

[0212] (2) The content of N-(2-amino-2-oxyethyl)acrylamide has a significant effect on the final adhesion performance.

[0213] When there is no N-(2-amino-2-oxyethyl) acrylamide (Comparative Example 5), the adhesive is only chemically cross-linked, showing brittleness and very low adhesion performance (shear tensile bearing strength is only 6 kPa, T-peel tensile bearing strength is only 15 J·m -2 , tensile strength is only 18 kPa, and wound closure strength is only 5 kPa). When the content of N-(2-amino-2-oxyethyl) acrylamide is very low (Comparative Example 6, 500 parts), the hydrogen bonding effect of N-(2-amino-2-oxyethyl) acrylamide itself is very weak after polymerization, and the strength of the adhesive body is very low (shear tensile bearing strength is only 20 kPa, T-peel tensile bearing strength is only 83 J·m -2 , tensile strength is only 44 kPa, and wound closure strength is only 15 kPa). Because when testing the adhesion performance, the main body breaks first, so the adhesion strength is low. When the content of N-(2-amino-2-oxyethyl) acrylamide is very high (Comparative Example 7, 4000 parts), the hydrogen bonding effect of N-(2-amino-2-oxyethyl) acrylamide itself is very strong after polymerization, and the hydrogen bonding effect with the tissue is weakened. In addition, the high-strength main body of the adhesive will also inhibit the reaction efficiency of acrylic acid-N-succinimide ester with tissue amino groups, thereby reducing the adhesion strength (shear tensile bearing strength is only 61 kPa, T-peel tensile bearing strength is only 232 J·m -2, tensile strength is only 134 kPa, and wound closure strength is only 34 kPa). By adding an appropriate amount of N-(2-amino-2-oxyethyl) acrylamide, the hydrogen bonding effect is enhanced, and the material exhibits higher tissue adhesion strength (shear tensile bearing strength up to 232 kPa, T-peel tensile bearing strength up to 754 J·m -2 , tensile strength up to 403 kPa, wound closure strength up to 136 kPa). Therefore, the preferred mass fraction of N-(2-amino-2-oxyethyl)acrylamide is 1000 to 3000 parts.

[0214] (3) The content of N-succinimidyl acrylate has a significant effect on the final adhesion performance.

[0215] When there is no acrylic acid-N-succinimide ester (Comparative Example 8), the adhesive and the tissue mainly rely on hydrogen bonds, and the adhesion performance is low (the shear tensile bearing strength is only 31 kPa, and the T-peel tensile bearing strength is only 152 J·m -2 , tensile strength is only 87 kPa, and wound closure strength is only 22 kPa). When the content of acrylic acid-N-succinimide ester is very low (Comparative Example 9, 50 parts), the adhesive has fewer groups that can react with the amino groups on the tissue, and the adhesion mechanism is mainly physical adhesion. At this time, the adhesion strength is still low (the shear tensile bearing strength is only 78 kPa, and the T-peel tensile bearing strength is only 263 J·m -2 , tensile strength is only 154kPa, and wound closure strength is only 87kPa). Because when the adhesion performance is tested, the adhesive and the tissue interface fall off, so the adhesion strength is low. When the content of acrylic acid-N-succinimide ester is very high (Comparative Example 10, 800 parts), although the adhesive has enough groups to react with the amino groups on the tissue, when too much acrylic acid-N-succinimide ester and N-(2-amino-2-oxyethyl) acrylamide are polymerized, the hydrogen bonding of N-(2-amino-2-oxyethyl) acrylamide itself is destroyed, resulting in a significant decrease in the strength of the body. Because when the adhesion performance is tested, the adhesive body is destroyed first, so the adhesion strength is reduced (the shear tensile bearing strength is only 85kPa, and the T-peel tensile bearing strength is only 321J·m -2 , tensile strength is only 184kPa, and wound closure strength is only 43kPa). After introducing an appropriate amount of acrylic acid-N-succinimide ester, the adhesive can form chemical adhesion with the tissue, so that the adhesion performance can be significantly improved (shear tensile bearing strength up to 300kPa, T-peel tensile bearing strength up to 1000J·m -2 , tensile strength up to 500 kPa, wound closure strength up to 200 kPa). Therefore, the preferred mass fraction of acrylic acid-N-succinimidyl ester is 100 to 500 parts.

[0216] Therefore, it can be concluded that high-strength tissue adhesion requires a combination of chemical adhesion and physical adhesion, and the two synergistically enhance tissue adhesion; high-strength adhesion is also related to the bulk strength of the adhesive. When debonding, not only is the interaction of the interface destroyed, but the bulk needs to withstand external forces and dissipate part of the energy. During the debonding process, the external force not only destroys the interface between the adhesive and the tissue, but also destroys the bulk of the adhesive. Therefore, based on the bulk of the adhesive and the interface adhesion mode, different debonding forms appear, such as bulk destruction and intact interface; bulk integrity and interface detachment; both interface and bulk are partially destroyed. However, in the formula disclosed in the present invention application, when the double bond grafting rate of sodium hyaluronate, the mass fractions of N-(2-amino-2-oxyethyl) acrylamide and acrylic acid-N-succinimide ester are simultaneously limited, the balance between the bulk strength of the adhesive and the interface adhesion can be achieved, and the highest adhesion strength of the adhesive can be achieved.

[0217] Test Example 2

[0218] A certain amount of adhesive precursor was placed on a glass plate, tilted at 30 degrees, and 20 μL of deionized water was added dropwise until the adhesive precursor fell off. The final mass of the precursor (m 1 ), and initial mass (m 0 ), and calculate the maximum liquid absorption rate.

[0219] Maximum liquid absorption rate = (m 1 -m 0 ) / m 0 ×100%

[0220] According to the above test method for the maximum liquid absorption rate, the maximum liquid absorption rate of the adhesive precursor Examples 1-4 and Comparative Examples 1-3 was tested to obtain Table 3.

[0221] Table 3 Maximum liquid absorption rate of adhesive precursors

[0222]

[0223] As can be seen from Table 3, the maximum liquid absorption rate of sodium alginate, inorganic salt components and adhesive precursors in the technical solution disclosed in the present invention is related. In the tests without sodium alginate and calcium sulfate (Comparative Example 1), only calcium sulfate and no sodium alginate (Comparative Example 2), and only sodium alginate and no calcium sulfate (Comparative Example 3), the liquid absorption rate cannot be tested because the adhesive precursor behaves as a liquid. As the sodium alginate content increases (Examples 1-4), the liquid absorption capacity is enhanced. This is because the increase in sodium alginate, on the one hand, increases the viscosity of the precursor, making the precursor more stable and not easy to dissolve; on the other hand, sodium alginate is a hydrophilic polysaccharide, which contains a large number of hydrophilic groups and can absorb more water. In addition, the physical crosslinking formed by the inorganic salt component and sodium alginate can well maintain the gel-like properties of swelling but not dissolving, thereby meeting the needs of the adhesive precursor to adhere to the tissue surface, smear filling, and absorb exudate.

[0224] Test Example 3

[0225] A certain amount of adhesive precursor was placed in the mold and irradiated with UV light for 1 min. Then the adhesive was soaked in deionized water and the weight of the adhesive at different times was recorded. When the weight no longer changed, it was the equilibrium mass (M 1 ), and initial mass (M 0 ) is converted to obtain the swelling ratio. Swelling ratio = (M 1 -M 0 ) / M 0 × 100%. According to the above swelling rate test method, the maximum swelling rate test was performed on Examples 5-11 and Comparative Examples 1, 4, 5 and 8, and Table 4 was obtained.

[0226] Table 4 Maximum swelling rate of adhesive after curing

[0227]

[0228] For the adhesion of wet tissue, excessive swelling of the adhesive itself will cause a change in volume and cause it to detach from the adhered tissue surface. Therefore, as a biological tissue adhesive, the swelling rate should be reduced as much as possible and controlled within 100%. As can be seen from Table 4, the swelling rate of the adhesive is related to the amount of sodium alginate, inorganic salts, double bond grafting rate of sodium hyaluronate, mass fraction of N-(2-amino-2-oxyethyl) acrylamide and mass fraction of acrylic acid-N-succinimide ester. The specific analysis is as follows:

[0229] (1) The physical cross-linked network of sodium alginate in the formula can not only maintain the gel-like form of the adhesive precursor before curing, but also, after curing, as a cross-linked network inside the adhesive, it can enhance the internal cross-linking degree of the adhesive and limit swelling. When there is no sodium alginate and no calcium sulfate (Comparative Example 1), the swelling rate is 328%, and when there is sodium alginate and calcium sulfate (Example 6), the swelling rate is 41%. This is because the physical cross-linked network formed by sodium alginate and inorganic salts limits swelling and reduces the swelling rate. Within the formula range disclosed in the invention application, the swelling rate can be maintained within 100%.

[0230] (2) Increasing the double bond grafting rate of sodium hyaluronate in the formula can effectively limit the swelling rate of the adhesive. When the double bond grafting rate of sodium hyaluronate is 0 (Comparative Example 4), the internal structure of the adhesive cannot form an effective macromolecular cross-linked network, and its swelling rate is 380%. By double-bond modification of sodium hyaluronate, a 10% grafting rate (Example 5) can limit the swelling rate of the adhesive to 56%. As the double bond grafting rate increases (Examples 6 and 7), the swelling rate of the adhesive further decreases. This is because the double-bond grafted sodium hyaluronate introduces chemical cross-linking sites into the adhesive structure, increases the cross-linking density, and leads to a decrease in the swelling rate; and as the grafting rate increases, the cross-linking density increases, and the swelling rate gradually decreases. Within the formula range disclosed in the invention application, the swelling rate can be maintained within 100%. Therefore, it is preferred that the grafting rate of sodium hyaluronate is 10 to 100%.

[0231] (3) N-(2-amino-2-oxyethyl) acrylamide in the formula has a strong hydrogen bonding effect, which can greatly resist the destruction of water molecules to the adhesive, thereby enhancing the cohesive force of the adhesive after curing, thereby resisting the swelling of the adhesive. In Comparative Example 5, since N-(2-amino-2-oxyethyl) acrylamide was not added, its swelling rate was 221%. With the addition of N-(2-amino-2-oxyethyl) acrylamide (Examples 8, 9 and 6), the swelling rate of the adhesive was significantly reduced and maintained within 80%, and as its proportion increased, the swelling rate gradually decreased. Within the scope of the formula disclosed in the invention application, the swelling rate within 100% can be maintained. Therefore, it is preferred that the mass fraction of N-(2-amino-2-oxyethyl) acrylamide is 1000 to 3000 parts.

[0232] (4) Acrylic acid-N-succinimide ester in the formula mainly plays a role in enhancing adhesion. As its proportion increases (Comparative Example 8, Examples 10, 6 and 11), the swelling rate of the adhesive increases slightly. This is because during the curing process, the acrylic acid-N-succinimide ester component will produce a steric hindrance effect on N-(2-amino-2-oxyethyl) acrylamide, affecting the hydrogen bonding of N-(2-amino-2-oxyethyl) acrylamide. However, this effect does not have a significant impact. According to the formula disclosed in the present application, the swelling rate of the embodiment is 22%-80%, thereby maintaining a small deformation after water absorption and avoiding tissue debonding caused by expansion. Within the formula range disclosed in the invention application, the swelling rate can be maintained within 100%. Therefore, it is preferred that the mass fraction of acrylic acid-N-succinimide ester is 100 to 500 parts.

[0233] For the adhesion of wet tissue, due to the diffusion of water molecules, the adhesive will swell and the body strength will be reduced; it will also penetrate into the interface, destroy the hydrogen bond adhesion of the interface, and finally cause rapid debonding. The in-situ gelling method adopted in the technical solution disclosed in the present invention application can eliminate the problem of interfacial water, because the adhesive itself is a water system, and the precursor has good water absorption capacity and can absorb interfacial water (Table 3). And through the optimization of the disclosed formula, the cured adhesive has a lower swelling rate and deformation (Table 4), so that the adhesive body is less damaged in water, and will not cause adhesion detachment due to volume change. According to the formula of the present invention, this adhesive can effectively solve the shortcomings of existing adhesives when applied to damaged biological tissues, including: 1) achieving efficient adhesion to tissues through physical and chemical methods; 2) constructing a gel-like adhesive precursor that can stay on irregular tissue surfaces; 3) achieving a high water absorption rate of the precursor, thereby effectively absorbing the residual water on the surface of wet tissues; 4) achieving a swelling rate of the adhesive lower than 100%, which can effectively avoid adhesion failure caused by swelling.

[0234] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A precursor of a gel-like curable strong adhesion tissue adhesive, characterized in that: Calculated by mass, the double bond grafting rate is 50%: 10 parts of sodium hyaluronate, 1000-3000 parts of N-(2-amino-2-oxyethyl) acrylamide, 100-500 parts of acrylic acid-N-succinimide ester, 100-400 parts of sodium alginate, 5-20 parts of inorganic salt, 1-50 parts of initiator, and 10,000 parts of solvent.

2. The precursor of a gel-like curable strong adhesion tissue adhesive according to claim 1, characterized in that: Calculated by mass, the following ingredients include 2000-3000 parts of N-(2-amino-2-oxyethyl) acrylamide, 200-500 parts of acrylic acid-N-succinimide ester, 200 parts of sodium alginate, 5-20 parts of inorganic salt, 1-50 parts of initiator and 10000 parts of solvent.

3. The precursor of a gel-like curable strong adhesion tissue adhesive according to claim 1, characterized in that: The inorganic salts include calcium sulfate, calcium chloride and calcium carbonate.

4. The precursor of a gel-like curable strong adhesion tissue adhesive according to claim 1, characterized in that: The initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt or α-ketoglutaric acid.

5. The precursor of a gel-like curable strong adhesion tissue adhesive according to claim 1, characterized in that: The solvent includes deionized water, phosphate buffer or Tris buffer.

6. A method for preparing a precursor of a gel-like curable strong adhesion tissue adhesive according to any one of claims 1 to 5, characterized in that: Prepared according to the following steps: 1) preparing sodium hyaluronate containing double bonds; 2) mixing the double-bond-containing sodium hyaluronate obtained in step 1), N-(2-amino-2-oxyethyl)acrylamide, acrylic acid-N-succinimidyl ester, an initiator and a solvent to obtain a mixed solution 1; 3) The mixed solution 1 obtained in step 2) is evenly mixed with sodium alginate and an inorganic salt to obtain a gel-like adhesive precursor.

7. The method for preparing a precursor of a gel-like curable strong adhesion tissue adhesive according to claim 6, characterized in that: The mixed solution 1 obtained in step 2) is a liquid and is not easy to stay on a smooth surface. The adhesive precursor obtained in step 3) is a gel, has good spreadability and conformal filling properties, can be applied to the gaps on the surface, has a liquid absorption rate of 230% to 300%, and can absorb the interfacial water on the surface of the wet tissue so that the wet tissue can adhere in situ.

8. A method for using a precursor of a gel-like curable strong adhesion tissue adhesive according to any one of claims 1 to 5, characterized in that: The gel-like adhesive precursor is applied to biological tissue and irradiated with an ultraviolet light source with a wavelength of 250 to 400 nm for less than 1 minute. The gel-like adhesive precursor is quickly cured and strongly adheres to the biological tissue.

9. The method for using the precursor of a gel-like curable strong-adhesive tissue adhesive according to claim 8, characterized in that: After being cured by light, the gel-like adhesive precursor has a maximum swelling rate of 22% to 80% in a wet environment.

10. The method for using the precursor of a gel-like curable strong-adhesive tissue adhesive according to claim 8, characterized in that: The gel adhesive precursor can produce an adhesive effect on skin, soft tissue organs and hard tissue after light curing, with a shear tensile bearing strength of 90 to 300 kPa and a T-peel tensile bearing strength of 350 to 1000 J·m -2 , tensile strength of 200-500 kPa and wound closure strength of 50-200 kPa.